Influence of high temperatures on the European earwig Forficula auricularia s.l. and the parasitoid Mastrus ridens, two natural enemies of the codling moth Cydia pomonella - Marie Perrin; Thomas Delattre; Nicolas Borowiec; Hazem Dib; Elodie Lecerf; Emile Melloul; Myriam Siegwart; Joffrey Moiroux (Biological Control)
A key concern for agriculture is that rising temperatures may disproportionately affect pests and their natural enemies, potentially leading to disruptions in their synchronization or population dynamics, thereby compromising biological control. This study examined whether the European earwig, Forficula auricularia sensu lato (Dermaptera: Forficulidae), a generalist predator native to France, and Mastrus ridens (Hymenoptera: Ichneumonidae), a recently introduced parasitoid of the codling moth Cydia pomonella (Lepidoptera: Tortricidae), can tolerate high temperatures and effectively control this pest under such conditions. Our measurements indicated that the parasitoid and predator were unable to complete their development at temperatures starting from 32 °C and 28 °C, respectively, whereas previous research has shown that the codling moth can develop at 35 °C. Unexpectedly, simulations indicated that + 4°C of global warming could reduce M. ridens generations during the summer in southeastern France. Furthermore, although the parasitism rate of M. ridens remained stable between 20 °C and 30 °C, its total fecundity declined at 28 °C, as did the predation rate of F. auricularia at 30 °C. Additionally, we observed that M. ridens susceptibility to two fungicides, sulfur and copper, and a bioinsecticide, azadirachtin, increased significantly with temperature. Our results thus highlight a significant risk of increased codling moth abundance during the hottest months, driven by the absence or reduced effectiveness of their natural enemies. This underscores the urgent need to implement measures to protect these beneficial organisms under climate change, such as creating microclimatic refuges and reducing the use of pesticides.